Pragmatikkens rolle i et morfologisk funderet genussystem i yngre middelskånsk - Petersen, Kathrine Thisted (Ny forskning i grammatik, 2016)
In Old Danish (c800-c1525), masculine, feminine, and neuter nouns were used to denote humans, animals, things, and abstract categories. In Early Modern Danish (c1525-c1700), however, the masculine and the feminine merged into a common gender, confining the anaphoric and cataphoric personal pronouns han ‘he’ and hun ‘she’ to nouns denoting humans. This paper points out an early pragmatically based use of gender in the Scanian text Sjælens Trøst ‘Comfort of the Soul’ in manuscripts C 529 and A 109 from c1425. From a Christian point of view, the noun afgudh ‘idol’ is used as a neuter and thereby objectified, unlike the masculine noun gudh ‘God’. This use of the neuter is in all likelihood one of the first steps on the way from a primarily morphologically based three-gender system to a primarily semantically based two-gender system which distinguishes between human and non-human nouns.